Dental deafferentation as an etiologic factor of taste dysfunction in male Wistar rats - Patiño Paúl, Alejandro Gutiérrez (2024)
Objective: To evaluate the influence of dental deafferentation (DD) on the sense of taste in male Wistar rats using the taste reactivity test (TRG). Materials and methods: An experimental study was conducted on ten Wistar rats, following ARRIVE 2.0 guidelines. They were randomized and assigned to a control or experimental group, and both groups' cannulae for the TRG were implanted. In the experimental group, exodontia of the three upper molars on the right side was performed. On the second or third day, GRT was started (day 1) by infusing 1 M of a sweet substance (ingestive) and 3 mM of a bitter substance (aversive) at a rate of 1 mL in 1 minute. This TRG was repeated on days 7, 14, and 21. Ingestive and aversive responses were scored for 1 minute. The data were processed in the SPSS v. 26 statistical package. The Mann-Whitney U test was used to identify differences, and the magnitude of the difference was calculated using Rosenthal's r. Results: Ingestive responses to sucrose were obtained on day 1 (p > 0.05); different responses were obtained on the other days: day 7 (p = 0.05), day 14 (p = 0.009), and day 21 (p = 0.009). Likewise, aversive responses to denatonium benzoate (BD) were obtained on days 1, 7, and 21 (p > 0.05); this was different on day 14 (p = 0.05). Conclusions: We found a difference in median ingestive responses to sucrose and aversive responses to BD in male Wistar rats due to DD.